National Diabetes Plans: can they support changes in health care systems to strengthen diabetes prevention and care? - Jelka Zaletel; Milivoj Piletic; Jaana Lindström; Andrea Icks; Ulrike Rothe; Monica Sørensen; Marina Maggini (Istituto Superiore di Sanità, 2015)
Healthcare systems do not fit well with the "modern" patient, who has a right to autonomy and self-determination. The services that are designed and delivered in policy contexts are not prone to encourage innovation. National Diabetes Plans, defined as "any formal strategy for improving diabetes policy, services and outcomes that encompass structured and integrated or linked activities which are planned and co-ordinated nationally and conducted at the national, regional, and local level", may hold a great potential not only to improve prevention and care for type 2 diabetes, but also for transforming healthcare delivery. Today, changes to adapt healthcare delivery tend to be implemented within existing provider structures, with limited understanding of specific context, structures, processes and potential for change. National Diabetes Plan can be a diagnostic tool for barriers, can be a driver for planning the change, and can help develop capacities and competences that are needed to strengthen healthcare systems to better address health promotion and chronic diseases.